Risk-based determination of polder height against storm surge Hazard in the south-west coastal area of Bangladesh. (December 2020) - Zaman, Shamrita; Mondal, M. Shahjahan
Abstract: Bangladesh was introduced with the polder system during 1960s to secure agricultural production from salinity intrusion. Existing polder design practice follows traditional return-period based approach. The article introduces a risk-based framework to determine optimal polder level in the coastal area of Bangladesh. Distinguishable features of risk-based framework over previous method is its inclusion of risk cost and optimal project size. Storm surge flooding was considered as the hazard intensity in this study. Agricultural losses due to storm surge flooding were factorized to get total losses. The optimum level of the polder was determined by summing up the annualized costs of raising polder and the risk cost due to storm surge flooding. The optimal polder level was found to be about 5.63 mPWD with a return period of about 37 years. The optimum design return-period for the polder in Bangladesh is considerably low compared to the current global design practices. This underscores the local peculiarities of the area (e.g., land use, economic activities, hazard sensitivity) in balancing incremental investment costs with reduced risk costs in a risk-based concept. The demonstration of the risk-based concept that is made for designing a coastal polder has potential for replication in other infrastructure designs.